Clinical outcomes of ramucirumab plus docetaxel in the treatment of patients with non-small cell lung cancer after immunotherapy: a systematic literature review - Garon, Edward B.; Visseren-Grul, Carla; Rizzo, Maria Teresa; Puri, Tarun; Chenji, Suresh; Reck, Martin (Frontiers in Oncology, 2023)
In the REVEL trial, ramucirumab plus docetaxel demonstrated significant improvements in overall survival (OS), progression free survival (PFS), and overall response rate (ORR) compared with placebo plus docetaxel for treatment of metastatic non-small cell lung cancer (NSCLC) that progressed during or after platinum-based chemotherapy. Since the approval of ramucirumab plus docetaxel, immune checkpoint inhibitors (ICIs), either as single agents or in combination with chemotherapy, have become the standard of care for first-line treatment of patients with advanced NSCLC. However, efficacy and safety data for ramucirumab plus docetaxel after prior ICI treatment from randomized controlled clinical studies are lacking. Following PRISMA guidelines, a systematic literature review was performed. Electronic databases and select international oncology conference proceedings were searched. Studies published between 01 January 2014 and 01 July 2022, which evaluated 2 efficacy outcomes (and included at least 1 time-to-event endpoint) or safety outcomes of RAM+DTX in NSCLC that progressed after prior ICI treatment, were identified. Twelve studies were included in the analysis. Two treatment groups were selected: ramucirumab plus docetaxel after prior ICI ± chemotherapy (RAM+DTX ICI pre-treated) and ramucirumab plus docetaxel after prior chemotherapy only (RAM+DTX ICI naïve). OS, PFS, ORR, disease control rate (DCR), and safety data were extracted and descriptively summarized across both treatment groups. The pooled weighted median PFS and median OS were 5.7 months (95% confidence interval [CI]: 3.9 6.8) and 11.2 months (95% CI: 7.5 17.5), respectively, in the RAM+DTX ICI pre-treated group and 3.8 months (95% CI: 2.3 4.1) and 13.5 months (95% CI: 8 24.0), respectively, in the RAM+DTX ICI naïve group. The ORR and DCR ranged from 20.9% to 60.0% and from 62.4% to 90.0%, respectively, in the RAM+DTX ICI pre-treated group and from 17.7% to 20.0% and from 57.1% to 75.0%, respectively, in the RAM+DTX ICI naïve group. The safety profile across studies was consistent between both treatment groups, and no new safety signals were reported. Cumulatively, these results support the combination of ramucirumab plus docetaxel as an effective and safe subsequent therapy for the treatment of patients with metastatic NSCLC with disease progression irrespective of previous ICI treatment.